Essential Oils of Aromatic and Medicinal Plants as Botanical Biocide for Management of Coconut Eriophyid Mite (Aceria guerreronis Keifer) - Susmita Patnaik; Kadambini Rout; Sasmita Pal; Prasanna Kumar Panda; Partha Sarathi Mukherjee; Satyabrata Sahoo (Psyche: A Journal of Entomology)
The present study investigated the efficiency of essential oils extracted from different aromatic and medicinal plant sources on Aceria guerreronis Keifer, one of the serious pests of coconut. The essential oils and the herbal extracts were prepared in two different formulations and were used both in laboratory and field conditions to assess the efficiency of the formulations against the coconut mite infestation. The field trial results showed that reduction in infestation intensity was found to vary between 73.44% and 44.50% at six different locations of trial farms with an average of 64.18% after four spells of treatment. The average number of live mites was higher in the third month old nuts both in the control as well as the treated nut samples. The laboratory experiments on the efficacy of botanical biocide showed that the time taken for dehydration and shriveling of body cells took only sixty seconds. The multilocational field trials revealed the overall efficiency of the biocide to significantly control the eriophyid mite in coconut crop in an ecofriendly and sustainable manner without adopting any chemical pesticide.